STRATEGI PEMASARAN PRODUK AIR MINUM DALAM KEMASAN “CI LEGON” OLEH PERUMDA AIR MINUM CILEGON MANDIRI DI WILAYAH KOTA CILEGON - Reina Yuniarsih; Candra Sigalingging (Journal Accounting International Mount Hope, 2024)
Bottled drinking water (AMDK) has now become a consumptive product for society. Various factors are the reasons why people choose to consume bottled drinking water, so that the need for bottled drinking water is currently continuing to increase and this is a potential business opportunity that is being looked at by Perumda Air Minum Cilegon Mandiri which has recently launched a bottled drinking water product with brand "Ci Legon". Collaborating with companies providing bottled drinking water contracting services using one stop contracting services makes it easier and more efficient for Perumda Air Minum Cilegon Mandiri to run this bottled drinking water business. This research was conducted with the aim of finding out what marketing strategies were carried out by Perumda Cilegon Mandiri in marketing the "Ci Legon" bottled drinking water product in the Cilegon City area. The research method used is a descriptive qualitative method. This research obtained data from interviews with sources, observation and documentation. The results of this research show that Perumda Air Minum Cilegon Mandiri uses a 4P marketing mix strategy to market Ci Legon bottled drinking water products.